Differential effects of domesticated and wild Capsicum frutescens L. on microbial community assembly and metabolic functions in rhizosphere soil - Wang, Can; Zhang, Yinghua; Wang, Shaoxiang; Lv, Xia; Xu, Junqiang; Zhang, Xueting; Yang, Qing; Meng, Fanlai; Xu, Bin (Frontiers in Microbiology, 2024)
Objective: Rhizosphere microorganisms play crucial roles in the growth and development of plants, disease resistance, and environmental adaptability. As the only wild pepper variety resource in China, domesticated Capsicum frutescens Linn.(Xiaomila) exhibits varying beneficial traits and affects rhizosphere microbial composition compared with its wild counterparts. In this study, we aimed to identify specific rhizosphere microbiome and metabolism patterns established during the 2 domestication process.Methods: The rhizosphere microbial diversity and composition of domesticated and wild C. frutescens were detected and analyzed by metagenomics. Non-targeted metabolomics were used to explore the differences of metabolites in rhizosphere soil between wild and domesticated C. frutescens.Results: We found that the rhizosphere microbial diversity of domesticated variety was significantly different from that of the wild variety, with Massilia being its dominant bacteria. However, the abundance of certain beneficial microbes such as Gemmatimonas, Streptomyces, Rambibacter and Lysobacter decreased significantly.The main metabolites identified in the wild variety included serylthreonine, deoxyloganic acid, vitamin C, among others. In contrast, those identified in the domesticated group were 4-hydroxy-L-glutamic acid and benzoic acid. Furthermore, the differentially enriched pathways were concentrated in tyrosine and tryptophan biosynthesis, histidine and purine-derived alkaloids biosynthesis, benzoic acid family, two-component system, etc.Conclusion: This study revealed that C. frutescens established specific rhizosphere microbiota and metabolites during domestication, which has important significance for the efficient utilization of beneficial microorganisms in breeding and cultivation practices.